Pengaruh Pembelajaran Kitab Washoya Terhadap Pembentukan Karakter Muslim Peserta Didik Di MTS Darussalam Sidoarjo - Nisfu Laili; Sufinatin Aisida (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Learning is a process of transferring knowledge provided by educators to students. So that students can gain additional insights into new knowledge. With the learning process can also shape the character of better students. To form a better character of students, moral learning is needed.This type of research is correlation or correlational research with a quantitative approach and data collection instruments using observation, documentation, and questionnaires. The data analysis technique uses descriptive analysis and hypothesis analysis.The results showed that: (1) washoya book learning at MTs. Darussalam Taman Sidoarjo is in a very high category, namely 81.35%, this is evidenced by analyzing the results of a questionnaire from 42 respondents. (2) the formation of Muslim character of students at MTs. Darussalam Taman Sidoarjo is in the high category, namely 70.84% this is evidenced by analyzing the results of a questionnaire from 42 respondents. (3) there is a significant influence between learning the book of washoya on the formation of Muslim character of students at MTs. Darussalam Sidodadi Taman Sidoarjo, as evidenced by the r2 coefficient value of 0.584.